Manejo de Meloidogyne incognita com espécies de Asteraceae - Ferreira, Isabel Cristina Madeira (2011)
The plant parasites nematodes, especially those of the genus Meloidogyne, are responsible for significant losses on agricultural production. The chemical control of these pathogens has caused serious environmental problems, and exposure of the applicator to a highly toxic and very expansive product, which becomes a decisive factor in the use of then. A viable alternative is the use of antagonistic plants, especially those of the Asteraceae family. The present study investigated in the first experiment, the host ability of Asteraceae family plants on Meloidogyne incognita and the effect of incorporation of dried aerial parts of these plants on the parasitism of this pathogen and on the second experiment, the effects in vitro and in vivo of the aqueous extracts of these species obtained in steps performed in the laboratory and greenhouse. The results of the first test showed that the Asteraceae plants evaluated varied as the host ability to M. incognita and the incorporation of plant residues of some species have an antagonistic potential. In the second trail was observed that all extracts were effective in reducing the M. incognita´s onset juvenile when compared to the control in in vitro tests, and in vivo tests demonstrated that, about of reproduction rate the extracts showed no statistical difference compared to control, but, when comparing different ways of applying them, it was observed that there was a statistical difference when Bull-herb and Mexican sunflower´s extracts were applied though foliar spraying and root treatment, however, there was no difference when these extracts were applied as irrigation on the substratum.